Notes on genus \(Laccotrephes\) Stål, 1866 (Hemiptera: Nepidae: Nepinae) from Vietnam, with the description of the female of \(Laccotrephes longicaudatus\) Nieser, Zettel & Chen, 2009 - Thi Phuong Uyen, Tran; Quang Cuong, Nguyen; Sergey, Ryndevich; Thi Hanh, Nguyen; Xuan Lam, Truong (Academia Journal of Biology, 2022)
A taxonomic study of the genus Laccotrephes Stål, 1866 from Vietnam is presented. Four species of the genus Laccotrephes have been identified in Vietnam: Laccotrephes pfeiferiae (Ferrari, 1888), Laccotrephes longicaudatus Nieser, Zettel & Chen, 2009, Laccotrephes simulatus Montandon, 1913 and Laccotrephes grossus (Fabricius, 1787). The female of the species Laccotrephes longicaudatus Nieser, Zettel & Chen is described for the first time. A key to the species of genus Laccotrephes known from Vietnam is also provided.